Seeds or Parasites? Clinical and Histopathological Features of Seeds and Parasites in the Appendix - Gizem ISSIN; Fatih DEMIR; Hasan Aktug SIMSEK; Diren Vuslat CAGATAY; Mahir TAYFUR; Ali KANDEMIR; Mecdi Gürhan BALCI (Federation of Turkish Pathology Societies, 2023)
Objective: Parasites and plant seeds may both be found in appendectomy specimens. Each plant seed has a different appearance and can thus exhibit wide variations under the microscope. Fragmented seeds may histologically mimic parasites. The differential diagnosis between seeds and parasites can be challenging in such cases. This study aimed to determine the incidence of parasites, seeds, and foreign bodies in appendectomy materials and highlight the most characteristic histopathological features associated with these structures. Material and Method: In this study, pathology slides of 9,480 patients, who underwent appendectomy between 2010 and 2021, were reviewed, and cases that contained parasites, seeds, or foreign bodies were identified. We reviewed the literature on seeds and parasites in appendectomy specimens. Results: Parasites were observed in 56 (0.6%) cases. Of these cases, 45 had Enterobius vermicularis (80%), and 11 had Taenia subspecies (20%). Plant seeds were observed in 47 cases (0.5%), and were macroscopically recognizable in 5 of them as olive, lemon, and cherry seeds. Parasites and seeds were usually observed in the lumen of appendix vermiformis, filled with abundant fecal materials. Conclusion: Seeds are seen in approximately 0.5% of the appendectomy specimens. Though rarely seen, the fragmented seed appearance may cause diagnostic difficulties. In this context, the key morphological features of parasites and plant seeds outlined in this study may be helpful in their differential diagnosis.